Correlation between cognitive abilitiy to the scientific creative thinking ability and scientific critical thinking ability on sound wave problems - S Karim; S Kartika; H Rusnayati; S Feranie A (International Conference on Mathematics and Science Education of Universitas Pendidikan Indonesia, 2018)
The aim of this study was to describe the correlation between cognitive ability to thesceintific creative thinking ability and scientific critical thinking ability on sound wavematerial. This study used an analytic descriptive method. The population of this study were11th grade students of SMAN 3 Cimahi academic year 2017-2018 which contained 20participant. The instrument used is a multiple choice questionnaire for cognitive tests and anessay questionnaire for the scientific and critical scientific thinking skill test. From theconducted study related to the correlation between cognitive ability to the sceintific creativethinking ability and scientific critical thinking ability showed a high correlation withcorrelation coefficient for cognitive ability with scientific creative thinking ability was 0,63 andcorrelation coefficient for cognitive ability with scientific critical thinking ability was 0,65.From the results it can be concluded that it has a good correlation.Which means that in solvingsound problem in this case student with high cognitive ability also have high scientific creativethinking ability and scientific critical thinking ability